The problems of use thermoplastic polymer waste to prodaction a wood plastic composites - Lyutyj, Pavlo; Bielova, Anna; Мarkiv Andriy (Forestry, Forest, Paper and Woodworking Industry, 2007)
In this editorial is writing about some problems which meet when prepare the wood plastic composites. Besides one of them is a bad interact thermoplastic matrix with the wood. Second big problem is using very high temperatures when prepare the wood plastic composites